Addressing the effect of concern with COVID-19 threat on prejudice towards immigrants: The sequential mediating role of need for cognitive closure and desire for cultural tightness. (March 2023) - Albarello, Flavia; Mula, Silvana; Contu, Federico; Baldner, Conrad; Kruglanski, Arie W.; Pierro, Antonio
Abstract: The link between threat and anti-immigrant prejudice is well-established. Relatedly, recent research has also shown that situational threats (such as concern with COVID-19 threat) increase anti-immigrant prejudice through the mediating role of desire for cultural tightness. This study aims to further our understanding of the psychological processes underlying the relation between concern with COVID-19 threat and increased negative attitudes towards immigrants by considering the mediational role of an individual epistemic motivation (i.e., the need for cognitive closure). A study was conducted on a large sample of Italian respondents covering all the Italian regions. Findings revealed that high concern with COVID-19 threat led to increased negative attitudes towards immigrants through the sequential mediating role of higher need for cognitive closure, leading in turn to higher desire for cultural tightness. Implications of these findings for a timely contextualized study of anti-immigrant prejudice will be highlighted.